Variabel-variabel yang Berpengaruh terhadap Keputusan Berkunjung Wisatawan Mancanegara dan Implikasinya terhadap Segmentasi Pasar, Targeting dan Positioning (Studi pada Daerah Tujuan Wisata Sulawesi Selatan) - Kamase, Jeni (Jurnal Aplikasi Manajemen, 2008)
The objective of research is to explain that: (1) tourist object, the promotion structure and infrastructure, and external factors affects the visiting decision of foreign tourist; (2) the identification of tourist market segments can be based on tourist perception about the expected benefit; (3) the meaningfully relationship develops between number of descriptor variables and tourist market segmentation of South Sulawesi; (4) the implication from each segment of tourist market for targeting and positioning in determining the tourist destination at South Sulawesi. Three regencies/cities become considered as tourist destination. The sampel of research includes foreign tourists visiting the regencies/cities tourist destination, reached 165 tourists. Statistic analysis used to test hypotheses involves regression analysis, factor analysis and cluster analysis. Results of research indicate that: (1) tourist attraction, promotion, structure and infrastructure, and external factors have significant effect on visiting decision variable: (2) from 34 benefits result in 10 tourist attraction factors; (3) from 165 cases revealed produces + potential market segments of tourist destination in South Sulawesi; (4) tourist perception about tourist destination in South Sulawesi. Regarding to the competitor and the expectation of tourist before visiting South Sulawesi, the market of South Sulawesi seems the most ideal for positioning it as beach and ethnic destination. The great potentials of both markers should be improved to be attained as target markers and to ensure the repositioning